2019
DOI: 10.1182/blood-2019-122411
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Single-Agent Inotuzumab Ozogamicin in Pediatric CD22-Positive Relapsed/Refractory Acute Lymphoblastic Leukemia: Preliminary Results of the ITCC-059 Study

Abstract: Background: Inotuzumab ozogamicin (InO) is an anti-CD22 antibody linked to calicheamicin, approved for relapsed/refractory (R/R) CD22+ B-cell precursor adult acute lymphoblastic leukemia (BCP-ALL) at starting dose of 1.8 mg/m2/course. A phase I study in pediatric patients (pts) is being performed and sponsored by Erasmus MC in collaboration with Pfizer, registered in the Dutch Trial Registry (NTR57360). Study design: Children aged 1-18 years with R/R CD22+ BCP-ALL (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The recent COG AALL1621 phase 2 trial (NCT02981628) studied the efficacy of inotuzumab in 48 uniformly treated children and AYAs in second or greater relapse of B‐ALL; preliminary outcomes show CR rates > 50%, nearly two thirds of whom achieved MRD negativity 21 . Preliminary results of the Dutch ITCC‐059 study also showed remarkable efficacy of inotuzumab in pediatric patients with rrALL with an 80% overall response rate and 79% of responding patients achieving an MRD‐negative CR 22 …”
Section: Introductionmentioning
confidence: 99%
“…The recent COG AALL1621 phase 2 trial (NCT02981628) studied the efficacy of inotuzumab in 48 uniformly treated children and AYAs in second or greater relapse of B‐ALL; preliminary outcomes show CR rates > 50%, nearly two thirds of whom achieved MRD negativity 21 . Preliminary results of the Dutch ITCC‐059 study also showed remarkable efficacy of inotuzumab in pediatric patients with rrALL with an 80% overall response rate and 79% of responding patients achieving an MRD‐negative CR 22 …”
Section: Introductionmentioning
confidence: 99%
“…Subsequent trials have demonstrated efficacy in Ph+ and pediatric R/R B-ALL. 32-34 Interestingly, rates of CR and MRD negativity were similar regardless of duration of prior remission, salvage attempt, and burden of disease. Chemotherapy (mini-hyper-CVD) added to InO also has been studied as a phase II with similar response and MRD negativity rates among responders, 78% and 82%, respectively.…”
Section: Therapy For Relapsed And/or Refractory Allmentioning
confidence: 91%
“…19 In a retrospective analysis of outcomes for 51 pediatric patients with R/R B-ALL treated with InO via a compassionate access program, the CR/CRi rate for those patients with overt marrow disease (n = 42) was 67%, of whom 71% had MRD < 0.01%. 20 A European phase I trial for pediatric patients reported an overall response (OR) rate of 80%, 79% of whom had MRD < 0.01%, 21 and a recent COG phase 2 single agent study (AALL1621) of InO for children with multiply R/R B-ALL demonstrated a CR/CRi rate of 58.3% (95% CI 43.2-72.4%) in 48 patients. 22 Of those with MRD reported (n = 26), 65.4% had MRD < 0.01%.…”
Section: Inotuzumab Ozogamicin In High-risk B-allmentioning
confidence: 99%